The Use of the Drill Method in Improving Students' Memory in Al-Quran Hadith Class - Ayu Maryani; Muawwiyah Muawwiyah; Fajriansyah Fajriansyah; Cecep Hilman (Journal of Pedagogi, 2025)
This research was driven by the need for effective teaching methods to enhance students' memory retention of Al-Qur'an Hadith material. The study aimed to analyze the effectiveness of the drill method in improving the memory retention of grade X students at MAN 1 Sukabumi City. A qualitative approach was employed, with data collected through in-depth interviews with teachers and students, classroom observations, and document studies of students' learning outcomes. The findings indicated that the drill method, which emphasizes systematic and structured repetition, significantly improved students' ability to memorize and recall Al-Qur'an Hadith material. Students demonstrated better retention and comprehension after repeated practice sessions. Teachers also noted increased student confidence and motivation in learning. Additionally, the structured nature of the drill method helps students internalize the material more effectively, reinforcing their long-term memory. The method was particularly beneficial in subjects requiring memorization, such as Al-Qur'an Hadith. Furthermore, students showed greater engagement in the learning process, as the repetitive exercises helped them track their progress. In conclusion, the drill method has been proven to be an effective learning strategy for enhancing students' memory retention, making it a valuable approach in religious education and other memory-based subjects